Research on the influence of college students’ participation in sports activities on their sense of inferiority based on self-esteem and general self-efficacy - Liu, Chu (Frontiers in Psychology, 2022)
College students need to face various problems and conflicts, and are prone to many negative emotions, such as depression, low self-esteem, social anxiety, low sense of belonging, lack of self-identity and so on. The generation of these bad emotions will bring unexpected negative effects to college students. Taking Chinese college students as the research object, this study analyzes the influence of sports participation on inferiority. Furthermore, we explored whether self-esteem and general self-efficacy mediated the relationship between physical activity and inferiority. In this study, 115 students were selected to conduct the experiment for 12 weeks. After reliability testing, the collected data were analyzed by multivariate analysis of variance to verify the research model. The results show that sports has a significant positive correlation with the reduction of college students' inferiority complex. What is important in this model is that self-esteem and general self-efficacy are enhanced during physical activity and decreased during inferiority complex. In addition, this study created three sports situations: competition group, entertainment group and control group. The comparison results show that competitive sports situation is better than leisure sports situation in terms of the influence on college students' inferiority complex. Through the theoretical and empirical research on college students' inferiority complex, it is concluded that sports is an effective means to reduce college students' inferiority complex.